The effects of genetic groups, and age on the chemical composition, physical properties, and somatic cell count of raw buffalo milk - Mettamehtar, K.; Tuntivisoottikul, K.; Takeungwongtrakul, S. (My University, 2022)
The genetic groups of the buffaloes influenced all the chemical compositional traits (P<0.05), and some physical properties, such as the percentage of citric acid content, and the milk urea nitrogen concentration (P<0.01). Milk from Swamp buffaloes had the highest percentage of fat content (11.1%) compared to purebred Murrah (7.9%) and 75%Murrah crossbreeds (8.2%), but it was not statistically different from the 50% Murrah crossbreeds (9.5%). Similar results were found in the percentages of protein, solid-not-fat, and total solids content. The purebred Murrah showed the highest average lactose content (4.9%), but it did not statistically differ from those of the 50% Murrah crossbreeds (4.6%) and Swamp buffalo (4.5%). The highest citric acid content was found in the Swamp buffaloes (0.20%), while the lowest of the trait was observed in the 100%Murrah. The Swamp buffaloes and the 50% Murrah crossbreeds had higher averages of urea concentration than the 100% Murrah and the 75% Murrah crossbreeds. The age of the animals in different genetic groups did not affect most of the studied traits (P>0.05), except the percentage of milk fat content, the percentage of citric acid and the percentage of urea concentration (P<0.05). The 50%Murrah crossbreeds and Swamp buffaloes which were older than 9 years old which had higher averages of fat content than the other groups. The highest citric acid content average was found in the 50%Murrah crossbreeds which were older than 9 years old, and the highest urea concentration average was detected in milk from the 50% Murrah crossbreeds which were younger than 7 years old.
Keywords: Citric acid; Milk urea nitrogen; Murrah; Raw milk properties; Swamp buffalo